Protocol for an Economic Evaluation of the Quitlink Randomized Controlled Trial for Accessible Smoking Cessation Support for People With Severe Mental Illness - Sweeney, Rohan; Moodie, Marj; Baker, Amanda L.; Borland, Ron; Castle, David; Segan, Catherine; Turner, Alyna; Attia, John; Kelly, Peter J.; Brophy, Lisa; Bonevski, Billie; Williams, Jill M.; et al. (Frontiers in Psychiatry, 2019)
Introduction: Smoking is a major cause of disease burden and reduced quality of life for people with severe mental illness (SMI). It places significant resource pressure on health systems and financial stress on smokers with SMI (SSMI). Telephone-based smoking cessation interventions have been shown to be cost-effective in general populations. However, evidence suggests SSMI are less likely to be referred to quitlines and little is known about the effectiveness and cost-effectiveness of such interventions that specifically target SSMI. The Quitlink randomised controlled trial for accessible smoking cessation support for SSMI aims to bridge this gap. This paper describes the protocol for evaluating the cost-effectiveness of Quitlink. Methods: Quitlink will be implemented in the Australian setting, utilising the existing mental health peer workforce to link SSMI to a tailored quitline service. The effectiveness of Quitlink will be evaluated in a clustered randomised controlled trial. A cost-effectiveness evaluation will be conducted alongside the Quitlink clustered RCT with incremental cost-effectiveness ratios (ICER) calculated for the cost ($AUD) per successful quit and quality adjusted life year (QALY) gained at 8 months compared with usual care from both healthcare system and limited societal perspectives. Financial implications for study participants will also be investigated. A modelled cost-effectiveness analysis will also be conducted to estimate future costs and benefits associated with any treatment effect observed during the trial. Results will be extrapolated to estimate the cost-effectiveness of rolling out Quitlink nationally. Sensitivity analyses will be undertaken to assess the impact on results from plausible variations in all modelled variables. Discussion: SSMI require additional support to quit. Quitlink utilises existing peer worker and quitline workforces and tailors quitline support specifically to provide that increased cessation support. Given Quitlink engages these existing skilled workforces, it is hypothesised that if found to be effective, it will also be found to be both cost-effective and scalable. This protocol describes the economic evaluation of Quitlink that will assess these hypotheses.